Management of dyslipidemia: a case study - Pragya Choubey; Ankita Thakur; Sakshi Sharma; Ashwani Upadhyaya (International Journal of Pharmacy and Analytical Research, 2022)
Dyslipidemia is one of the major pathological conditions. Most people will have no symptoms but having hyperlipidemia increase risk of developing fatty liver, cardiovascular disease and many other diseases. Sanitary life style and bad food habit plays important role to form unsaturated fat and at last raised lipid profile. We can refer dyslipidemia with Medovaha Srotodushti in Ayurvedic context. Plant sterols are very good sources that inhibit storage of unsaturated fat in our body. Curry leaf (Murraya koneigii) is a very common plant which is used in every house hold. Antilipidemic activity of this plant has already proved in various researches. The main objective of this study is management of dyslipidemia with curry leaf in a single case study.